Study of Ingavirin® Antiviral Activity against Mexican Pandemic Influenza Virus A/H1N1/2009 in vitro and in vivo - S. YA. Loginova; S. V. Borisevich; V. N. Shchukina; M. V. Lykov; G. V. Borisevich; V. P. Bondarev; V. E. Nebolsin; O. A. Sutochnikova; A. G. Chychalin (Антибиотики и Химиотерапия, 2020)
High in vitro and in vivo efficacy of Ingavirin® against the Mexican pandemic influenza virus A/H1N1/2009, strains A/California/ 04/2009 (H1N1) and A/California/07/2009 (H1N1) vs. the reference drug Arbidol® was studied and verified when used therapeutically and prophylactically.